Corrosion-induced brittle failure in reinforcing steel. (December 2017) - Sanchez, J.; Fullea, J.; Andrade, C.
Highlights: The mechanical behaviour of carbon steel rebars is correlated with the corrosion morphology. A criterion to assess existing structures is presented. The embrittlement is taken into account. Accelerated corrosion test could not be realistic. Abstract: Steel rebar corrosion is the main cause of reinforced concrete structure deterioration and shortened service life. A number of corrosion mechanisms induce geometric flaws in rebar, reducing its mechanical strength. Interstitial hydrogen, which lowers steel toughness, may also prompt embrittlement. This paper discusses the effect of local, pitting and corrosion stress on steel rebar performance. The findings show that rebar bearing strength depends on corrosion morphology and weight loss, which would explain the scatter in experimental results when the latter is the sole parameter studied.